Corak Tafsir Periode Pertengahan - Kholiq, Abdul; Ni’matul Kafiyah, Fitroh; Abdul Jabbar, Ibrahim (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2023)
The development of interpretation in the Middle Ages was dominated by science, which at that time was experiencing its heyday. During the 11th century, the interpretation of mufassir tended to be based on the interests and scientific background of the mufassir. The scientific background of the mufassirs, who have different specializations in their interpretations, gradually gives birth to at-Tafsir, or patterns in their interpretation. This study uses a literature study (library research) with qualitative methods and a descriptive approach to discuss the definition of interpretation patterns, the periodization of interpretations, various types of interpretations, and examples of patterns in interpretation. The result of this study is an explanation regarding the style of interpretation, which can be seen from the interpretation products of a mufassir or through the research of a mufassir himself. The research starts with the background of the mufassir, education, and the purpose of the mufassir in compiling a book of interpretations. The variety of colors or patterns of a mufassir in interpreting are grouped into six: fiqh pattern, lughowi pattern, scientific pattern, philosophical pattern, Sufi pattern, and adab ijtima'i pattern. There are many Mufassir who pursued various styles in the medieval period, such as Imam ath-Tabari with his Tafsir ath-Tabari with a fiqh style, Imam Fakhruddin ar-Razi with his Tafsir Mafatih al-Ghaib with a philosophical and scientific style, and Imam Abu Hayyan with his Tafsir Bahr al-Muhith lughowi pattern. The benefits of this research are expected to come in the form of scientific insights and enrich the scientific literacy of the Al-Qur'an interpretation. Also, be able to have an impact in the form of attracting the interest of other researchers to continue to develop similar research.